Estudo da modificação de bentonita para a remoção de fenol em águas produzidas na indústria de petróleo - Oliveira, Maryelzy Felipe David de (2009)
This study evaluates the inclusion of quaternary ammonium salt, bromide hexadecyl trimethyl ammonium (HDTMA-Br) on sodium bentonite to evaluate their performance on the adsorption of phenol present in produced water. It was observed an increase in d001 samples modified with HDTMA-Br by diffraction of X-rays, showing the intercalation of quaternary ammonium cations in the interlamellar layers of clay. Through the adsorption isotherms could be abserver adsorption behavior of sodium bentonite and organophilic bentonite produced in three different concentrations of HDTMA-Br for adsorption of phenol, which is the main phenolic compound found in the product water. Different concentrations of synthetic solutions of phenol were placed in contact with these adsorbents under the same conditions of agitation and temperature. The adsorbent showed adsorptive favorable, especially the clay modified with the highest concentration of HDTMA-Br, 150% CEC of clay, BEN30-14, with higher amounts of phenol adsorbed per gram of adsorbent (mg.g-1)